Viewing Omnibus Law's Policy in a Governance Ethics Perspective through Social Media Twitter - Dedi Kusuma Habibie; Sanny Nofrima; Prawira Yudha Pratama; Herdin Arie Saputra; Danang Kurniawan (Jurnal Public Policy, 2021)
Social media can quickly help people interact with the Government and use technology to turn communication into interactive dialogue. This study looks at Omnibus Law policies from government ethics through social media Twitter hashtag (#) Omnibus law. The method used in this research is qualitative, then data is collected from the Twitter hashtag using Nvivo12 Plus to analyze the data. This study's results reveal that the Hashtag (#) Omnibus Law's effectiveness is proven to be efficient in viewing data analysis through information dissemination on Nvivo12 Plus on Twitter to see policies and responses from the public who use the Hashtag (#) Omnibus Law.